Edge Analytics Select Proceedings of 26th International Conference ADCOM 2020 - Patgiri, Ripon; Bandyopadhyay, Sivaji; Borah, Malaya Dutta; Emilia Balas, Valentina; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book constitutes refereed proceedings of the 26th annual International Conference on Advanced Computing and Communications (ADCOM 2020). ADCOM, the flagship Systems Conference of the ACCS, is a major annual international meeting that draws leading scientists and researchers in computational and communications engineering from across industry and academia. The proceedings highlight the growing importance of large-scale systems engineering and discuss leading-edge research and trends. The main theme of ADCOM 2020 is Edge Analytics. The book includes novel contributions and latest developments from researchers across industry and academia who are working in security, privacy, and data analytics from both technological and social perspectives. The book serves as a valuable reference resource for academics and researchers across the globe.
Keywords: Telecommunication; Artificial intelligence; Communications Engineering, Networks; Artificial Intelligence; Artificial intelligence -- Congresses; Computer networks -- Congresses; Computer systems -- Congresses; Computers -- Congresses; Machine learning -- Congresses; Telecommunication -- Congresses